THE POLITICS OF POPULAR ISLAM: AN ETHNOGRAPHIC EXPLORATION OF ISLAMIC REVIVALISM IN PAKISTAN - Bilal, Muhammad (Politikologija religije, 2021)
In the post-9/11 scenario, the rise of the Taliban and their coalition with Al-Qaeda have engendered new discourses about Islam and Pakistan. In this paper, I present a multi-sited ethnography of Bari Imam, a popular Sufi shrine in Pakistan while re-evaluating certain suppositions, claims and theories about popular Islam in the country. Have militarization, Shariatisation, and resurgence movements such as the Taliban been overzealously discussed and presented as the representative imageries of Islam? I also explore the Sufi dynamics of living Islam, which I will suggest continue to shape the lives and practices of the vast majority of Pakistani Muslims. The study suggests that general unfamiliarity of people outside the subcontinent with the Sufi attributes of living Islam, together with their lack of knowledge of the varieties of identification, observance and experience of Islam among Pakistanis, limit not only their understanding of the land of Pakistan, but also their perception of its people and their faith (Islam).